PROMOTING MEASURES FOR PREVENTING CONFLICTS BETWEEN FARMERS AND CATTLE HERDSMEN IN RURAL COMMUNITIES OF BENUE STATE, NIGERIA - EN, MBAH; NE, AMAH; BS, MITU (Innovare Journal of Agricultural Sciences, 2021)
Objective: The study was carried out to identify measures for preventing conflicts between farmers and cattle herdsmen in rural communities of Benue State, Nigeria. The specific objectives were to: Describe the socioeconomic characteristics of the respondents; ascertain the causes of conflict between farmers and cattle herdsmen in the study area; and identify measures required for preventing conflicts between farmers and cattle herdsmen. Methods: Data were collected from a sample of one hundred and eighteen (118) respondents in four communities in the study area using a well-structured questionnaire. Descriptive statistics such as frequency, percentage, mean, and standard deviation were used for data analysis. Results: Majority (90.7%) of the respondents had farming as a major source of livelihood, 55.1% were male while 62.7% were married. Damage to crops by cattle (x̄=2.72), uncontrolled grazing (x̄=2.52), herders claiming the land as common property (x̄=2.40), and destruction of farmland (x̄=2.30) were the major causes of conflicts. Measures required for preventing conflicts between farmers and cattle herdsmen include herdsmen education on the effects of the conflict (x̄=2.21), signing of a peace accord by both parties (x̄=2.12), establishment of ranches (x̄=2.06), implementation of law prohibiting open grazing (x̄=2.05), and disarming both parties (x̄=1.87). Conclusion: Educating farmers and herdsmen on the effects of the conflict, signing of a peace accord agreement by both parties, establishment of ranches, implementation of law prohibiting open grazing, and disarming both parties were measures required for preventing conflicts between farmers and cattle herdsmen. It is recommended that law enforcement agencies should enforce law on open grazing to avoid conflicts between farmers and cattle herdsmen in the area.